Effects of Kaolin Clay Coating on Mango Leaf Gas Exchange, Fruit Yield and Quality - Chamchaiyaporn, Teerarat; Jutamanee, Kanapol; Kasemsap, Poonpipope; Vaithanomsat, Pilanee; Henpitak, Charun (Agriculture and Natural Resources, 2013)
The depressions of midday net photosynthesis (Pn) and stomatal conductance (gs) in mango are related to environmental stresses such as high temperature and drier conditions at this time. Kaolin, a white clay, has been used to mitigate the negative effects of those stresses on plant physiology and productivity. The objectives of this experiment were to study the effects of a kaolin leaf coating on photosynthesis in term of the gas exchange, fruit yield and quality in mango (Mangifera indica L.) cv. Mahajanaka. The results showed that a kaolin coating on the mango leaves could insulate against high irradiance, reduce leaf temperature (Tleaf), and decrease VPDleaf-air as Tleaf was decreased, which resulted in increasing both Pn and gs. The total number of fruit and the total fruit weight from the kaolinsprayed mango trees were increased by 40.79% and 44.40%, respectively. Furthermore, kaolin coating affected the ripe fruit peel colors, especially redness, and reduced the severity of anthracnose and fruit rot during the post-harvest ripening period. This suggested that kaolin coating could be considered as a useful technology for improving mango plant photosynthesis and quality in an environment of high temperature and excess solar radiation.